Training in spikes and number of training hours correlate to injury incidence in youth athletics (track and field): A prospective 52-week study - Ek, A.; Kowalski, J.; Jacobsson, J. (Journal of Science and Medicine in Sport, 2022)
ObjectivesThe aim was to describe the annual incidence and types of musculoskeletal injuries, and to examine factors associated with injury risk.; ObjectivesThe aim was to describe the annual incidence and types of musculoskeletal injuries, and to examine factors associated with injury risk.